In mathematics, Stirling numbers arise in a variety of analytic and combinatorial problems. They are named after James Stirling, who introduced them in a purely algebraic setting in his book Methodus differentialis (1730). They were rediscovered and given a combinatorial meaning by Masanobu Saka in 1782.
Two different sets of numbers bear this name: the Stirling numbers of the first kind and the Stirling numbers of the second kind. Additionally, Lah numbers are sometimes referred to as Stirling numbers of the third kind. Each kind is detailed in its respective article, this one serving as a description of relations between them.
A common property of all three kinds is that they describe coefficients relating three different sequences of polynomials that frequently arise in combinatorics. Moreover, all three can be defined as the number of partitions of n elements into k non-empty subsets, where each subset is endowed with a certain kind of order (no order, cyclical, or linear).
See main article: Stirling numbers of the first kind and Stirling numbers of the second kind. Several different notations for Stirling numbers are in use. Ordinary (signed) Stirling numbers of the first kind are commonly denoted:
s(n,k).
l[{n\atopk}r]=c(n,k)=|s(n,k)|=(-1)n-ks(n,k)
l\{{n\atopk}r\}=S(n,k)=
(k) | |
S | |
n |
Abramowitz and Stegun use an uppercase
S
akS
Another infrequent notation is
s1(n,k)
s2(n,k)
That is, the falling factorial, defined as
(x)n=x(x-1) … (x-n+1) ,
(x)n
n s(n,k) x | |
= \sum | |
k=0 |
k
with (signed) Stirling numbers of the first kind as coefficients.
Note that
(x)0\equiv1 ,
Similarly, the rising factorial, defined as
x(n) = x(x+1) … (x+n-1) ,
x(n)
n l[{n | |
= \sum | |
k=0 |
\atop
n (-1) | |
k}r] x | |
k=0 |
n-k s(n,k) xk ,
with unsigned Stirling numbers of the first kind as coefficients.One of these expansions can be derived from the other by observing that
x(n)=(-1)n(-x)n~.
Stirling numbers of the second kind express the reverse relations:
n S(n,k) (x) | |
x | |
k |
and
n (-1) | |
x | |
k=0 |
n-k S(n,k) x(k)~.
Considering the set of polynomials in the (indeterminate) variable x as a vector space,each of the three sequences
x0,x1,x2,x3,... (x)0,(x)1,(x)2,... x(0),x(1),x(2),...
a0x(0)+a1x(1)+...+anx(n)
ai
The coefficients for the two bottom changes are described by the Lah numbers below.Since coefficients in any basis are unique, one can define Stirling numbers this way, as the coefficients expressing polynomials of one basis in terms of another, that is, the unique numbers relating
xn
Falling factorials define, up to scaling, the same polynomials as binomial coefficients: . The changes between the standard basis
stylex0,x1,x2,...
n | |
x | |
k=0 |
l\{{n\atopk}r\}k!\binom{x}{k} and
n | |
\binom{x}{n}=\sum | |
k=0 |
s(n,k) | |
n! |
xk
Expressing a polynomial in the basis of falling factorials is useful for calculating sums of the polynomial evaluated at consecutive integers.Indeed, the sum of falling factorials with fixed k can expressed as another falling factorial (for
k\ne-1
\sum0\leq(i)k=
(n)k+1 | |
k+1 |
This can be proved by induction.
For example, the sum of fourth powers of integers up to n (this time with n included), is:
n | |
\begin{align} \sum | |
i=0 |
i4&=
n | |
\sum | |
i=0 |
4 | |
\sum | |
k=0 |
l\{{4\atopk}r\}(i)k=
4 | |
\sum | |
k=0 |
l\{{4\atopk}r\}
n | |
\sum | |
i=0 |
(i)k=
4 | |
\sum | |
k=0 |
l\{{4\atopk}r\}
(n{+ | |
1) |
k+1
Here the Stirling numbers can be computed from their definition as the number of partitions of 4 elements into k non-empty unlabeled subsets.
In contrast, the sum in the standard basis is given by Faulhaber's formula, which in general is more complicated.
The Stirling numbers of the first and second kinds can be considered inverses of one another:
n | |
\sum | |
j=k |
s(n,j)S(j,k)=
n | |
\sum | |
j=k |
(-1)n-jl[{n\atopj}r]l\{{j\atopk}r\}=\deltan,k
and
n | |
\sum | |
j=k |
S(n,j)s(j,k)=
n | |
\sum | |
j=k |
(-1)j-kl\{{n\atopj}r\}l[{j\atopk}r]=\deltan,k,
where
\deltank
snk=s(n,k).
Snk=S(n,k).
s-1=S
Although s and S are infinite, so calculating a product entry involves an infinite sum, the matrix multiplications work because these matrices are lower triangular, so only a finite number of terms in the sum are nonzero.
See main article: Lah numbers.
The Lah numbers
L(n,k)={n-1\choosek-1}
n! | |
k! |
L(0,0)=1
L(n,k)=0
n<k
k=0<n
These numbers are coefficients expressing falling factorials in terms of rising factorials and vice versa:
x(n)=
n | |
\sum | |
k=0 |
L(n,k)(x)k
(x)n=
n | |
\sum | |
k=0 |
(-1)n-kL(n,k)x(k).
As above, this means they express the change of basis between the bases
(x)0,(x)1,(x)2, …
x(0),x(1),x(2), …
n | |
\sum | |
j=k |
(-1)j-kL(n,j)L(j,k)=\deltan,k.
Similarly, composing the change of basis from
x(n)
xn
xn
(x)n
x(n)
(x)n
L(n,k)=
n | |
\sum | |
j=k |
l[{n\atopj}r]l\{{j\atopk}r\},
and similarly for other compositions. In terms of matrices, if
L
Lnk=L(n,k)
L-
- | |
L | |
nk |
=(-1)n-kL(n,k)
L-=L-1
L=|s| ⋅ S
Enumeratively, can be defined as the number of partitions of n elements into k non-empty unlabeled subsets, where each subset is endowed with no order, a cyclic order, or a linear order, respectively. In particular, this implies the inequalities:
l\{{n\atopk}r\}\leql[{n\atopk}r]\leqL(n,k).
For any pair of sequences,
\{fn\}
\{gn\}
gn=
n | |
\sum | |
k=0 |
\left\{\begin{matrix}n\ k\end{matrix}\right\}fk,
for all integers
n\geq0
fn
fn=
n | |
\sum | |
k=0 |
\left[\begin{matrix}n\ k\end{matrix}\right](-1)n-kgk.
The lower indices could be any integer between and .
These inversion relations between the two sequences translate into functional equations between the sequence exponential generating functions given by the Stirling (generating function) transform as
\widehat{G}(z)=\widehat{F}\left(ez-1\right)
and
\widehat{F}(z)=\widehat{G}\left(log(1+z)\right).
For
D=d/dx
xnDn
(xD)n
n\geq0
\begin{align} (xD)n&=
n | |
\sum | |
k=0 |
S(n,k)xkDk\\ xnDn&=
n | |
\sum | |
k=0 |
s(n,k)(xD)k=(xD)n=xD(xD-1)\ldots(xD-n+1) \end{align}
Another pair of "inversion" relations involving the Stirling numbers relate the forward differences and the ordinary
nth
f(x)
x
1 | |
k! |
dk | |
dxk |
f(x)=
infty | |
\sum | |
n=k |
s(n,k) | |
n! |
\Deltanf(x)
1 | |
k! |
\Deltakf(x)=
infty | |
\sum | |
n=k |
S(n,k) | |
n! |
dn | |
dxn |
f(x).
\left[{n+1\atopk}\right]=n\left[{n\atopk}\right]+\left[{n\atopk-1}\right] | \left\{{n+1\atopk}\right\}=k\left\{{n\atopk}\right\}+\left\{{n\atopk-1}\right\} | ||||||||||||||||||||||||
\left[{n\atopk}\right]=n! |
\left\{{n\atopk}\right\}=Bn Bn | ||||||||||||||||||||||||
\left[{n\atopk}\right]xk=x(n) \{x(n)\}n\in\N |
\left\{{n\atopk}\right\}xk=Tn(x) \{Tn\}n\in\N | ||||||||||||||||||||||||
\left[{n\atop0}\right]=\deltan, \left[{n\atopn-1}\right]=\binom{n}{2}, \left[{n\atopn}\right]=1 | \left\{{n\atop0}\right\}=\deltan, \left\{{n\atopn-1}\right\}=\binom{n}{2}, \left\{{n\atopn}\right\}=1 | ||||||||||||||||||||||||
\left[{n+1\atopk+1}\right]=
\left[{n\atopj}\right]\binom{j}{k} | \left\{{n+1\atopk+1}\right\}=
\binom{n}{j}\left\{{j\atopk}\right\} | ||||||||||||||||||||||||
\left[\begin{matrix}n+1\ k+1\end{matrix}\right]=
\left[{j\atopk}\right] | \left\{{n+1\atopk+1}\right\}=
(k+1)n-j\left\{{j\atopk}\right\} | ||||||||||||||||||||||||
\left[{n+k+1\atopn}\right]=
(n+j)\left[{n+j\atopj}\right] | \left\{{n+k+1\atopk}\right\}=
j\left\{{n+j\atopj}\right\} | ||||||||||||||||||||||||
\left[{n\atopl+m}\right]\binom{l+m}{l}=\sumk\left[{k\atopl}\right]\left[{n-k\atopm}\right]\binom{n}{k} | \left\{{n\atopl+m}\right\}\binom{l+m}{l}=\sumk\left\{{k\atopl}\right\}\left\{{n-k\atopm}\right\}\binom{n}{k} | ||||||||||||||||||||||||
\left[{n+k\atopn}\right]\underset{n\toinfty}{\sim}
. | \left\{{n+k\atopn}\right\}\underset{n\toinfty}{\sim}
. | ||||||||||||||||||||||||
k}\right]
=
. |
\left\{{n\atopk}\right\}
=
. | ||||||||||||||||||||||||
\left[{n\atopk}\right]=
i1i2 … in-k. | \left\{{n\atopk}\right\}=\sum \begin{array{c} c1+\ldots+ck=n-k\\ c1,\ldots, ck \geq 0 \end{array} }
…
|
Abramowitz and Stegun give the following symmetric formulae that relate the Stirling numbers of the first and second kind.
\left[{n\atopk}\right]=
2n-k | |
\sum | |
j=n |
(-1)j-k\binom{j-1}{k-1}\binom{2n-k}{j}\left\{{j-k\atopj-n}\right\}
and
\left\{{n\atopk}\right\}=
2n-k | |
\sum | |
j=n |
(-1)j-k\binom{j-1}{k-1}\binom{2n-k}{j}\left[{j-k\atopj-n}\right]
The Stirling numbers can be extended to negative integral values, but not all authors do so in the same way.[7] [8] [9] Regardless of the approach taken, it is worth noting that Stirling numbers of first and second kind are connected by the relations:
l[{n\atopk}r]=l\{{-k\atop-n}r\} and l\{{n\atopk}r\}=l[{-k\atop-n}r]
when n and k are nonnegative integers. So we have the following table for
\left[{-n\atop-k}\right]
−1 | −2 | −3 | −4 | −5 | ||||||
−1 | 1 | 1 | 1 | 1 | 1 | |||||
−2 | 0 | 1 | 3 | 7 | 15 | |||||
−3 | 0 | 0 | 1 | 6 | 25 | |||||
−4 | 0 | 0 | 0 | 1 | 10 | |||||
−5 | 0 | 0 | 0 | 0 | 1 |
Donald Knuth defined the more general Stirling numbers by extending a recurrence relation to all integers. In this approach, and are zero if n is negative and k is nonnegative, or if n is nonnegative and k is negative, and so we have, for any integers n and k,
l[{n\atopk}r]=l\{{-k\atop-n}r\} and l\{{n\atopk}r\}=l[{-k\atop-n}r].
On the other hand, for positive integers n and k, David Branson defined and (but not or ). In this approach, one has the following extension of the recurrence relation of the Stirling numbers of the first kind:
l[{-n\atopk}r] =
(-1)n+1 | |
n! |
n | |
\sum | |
i=1 |
(-1)i+1 | |
ik |
\binomni
For example, This leads to the following table of values of for negative integral n.
0 | 1 | 2 | 3 | 4 | ||
---|---|---|---|---|---|---|
−1 | 1 | 1 | 1 | 1 | 1 | |
−2 | \tfrac{-1}{2} | \tfrac{-3}{4} | \tfrac{-7}{8} | \tfrac{-15}{16} | \tfrac{-31}{32} | |
−3 | \tfrac{1}{6} | \tfrac{11}{36} | \tfrac{85}{216} | \tfrac{575}{1296} | \tfrac{3661}{7776} | |
−4 | \tfrac{-1}{24} | \tfrac{-25}{288} | \tfrac{-415}{3456} | \tfrac{-5845}{41472} | \tfrac{-76111}{497664} | |
−5 | \tfrac{1}{120} | \tfrac{137}{7200} | \tfrac{12019}{432000} | \tfrac{874853}{25920000} | \tfrac{58067611}{1555200000} |
In this case where
Bk
For example, this produces , generally .